Theoretical on the physical status of the student knowledge monitor (Eurasian Scientific Herald, 2022)
The article summarizes the actual problems of improving theoretical knowledge and practical skills that students of general education schools should be taught about the content of the status of student Jim one of the pressing problems in the context of the current program of Physical Culture Education in the process of Physical Culture Education. It is intended for future Bachelors, Masters and teachers of Physical Culture and sports specialists